1984
DOI: 10.1104/pp.74.1.81
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of Chilling-Induced Water Stress by Abscisic Acid-Induced Changes in Root Hydraulic Conductance

Abstract: ABSTRACrPretreatment of soybean (Glycine max L. var Ransom) root systems with abscisic acid (ABA) ameliorates the deleterious effect of low temperatures on root hydraulic conductance. ABA treatment of root systems subsequently chilled to 10°C with shoots at 25°C resulted in higher leaf water potentials and lower stomatal resistances. If the root systems are left at 25C, ABA causes stomatal closure. Membrane alterations are suggested as a mechanism for the ABA action in plant response to chilling stress.Abscisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
1

Year Published

1985
1985
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(34 citation statements)
references
References 10 publications
0
33
1
Order By: Relevance
“…The L of intact plants was estimated as the ratio of transpiration rate to absolute value of *w. Transpiration is expressed here as volume flux per unit root length, as the root provides the major resistance to water flow, especially in chilled seedlings (1,5,6). In fully-nourished plants, L was high at root temperatures 220°C, but it decreased sharply in a narrow temperature range centered on about 15C (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The L of intact plants was estimated as the ratio of transpiration rate to absolute value of *w. Transpiration is expressed here as volume flux per unit root length, as the root provides the major resistance to water flow, especially in chilled seedlings (1,5,6). In fully-nourished plants, L was high at root temperatures 220°C, but it decreased sharply in a narrow temperature range centered on about 15C (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although induction of chilling tolerance with ABA in maize plants has not been demonstrated (29), ABA has been reported to increase chilling tolerance of eggplant, soybean, and cucumber seedlings (5,15,21), cotton cotyledonary discs (19,20), and maize callus culture (4). The inability of ABA to induce chilling tolerance in maize plants could result from lack of uptake or biodegradation of applied exogenous ABA.…”
Section: Discussionmentioning
confidence: 99%
“…Among these changes are increases in the degree of unsaturation of fatty acids in the phospholipids of membranes in a number of plants (26). The (17) reported that ABA-induced changes in root hydraulic conductance alleviated the chilling-induced water stress in soybean. Rikin and Richmond (20) found that ABA applications to whole cucumber seedlings 15 h before the cotyledons were detached and exposed to chilling temperatures, resulted in less ion leakage than from the nonsprayed, chilled control plants.…”
Section: Discussion Chilling Injury and Temperature Conditioningmentioning
confidence: 99%